Comparative analysis of cytological changes in the buccal mucosa among traditional cigarette and electronic cigarette users - Magdi M. Salih; Thamer A. Tamr; Tariq E. Elmissbah; Sabah M. Hanafy; Haytham A. Dahlawi; Eman H. Khalifa (Tobacco Induced Diseases)
Introduction The study aimed to evaluate cytological changes in the buccal mucosa among traditional cigarette smokers and electronic cigarette smokers.